New tourism product forecasting - A study of different potential markets - Noratikah, Abu; Sarah, Mohd Khaidi; Noryanti, Muhammad (AIP Publishing, 2021)
Mushrooming of new tourism products in Malaysia and their shutdown in the short term are the sign of ineffective forecast. Besides, no new development in tourism products causes the decline of the number of visitors to the attractions. This study proposes an application of a grey Bass diffusion model to forecast the new tourism product using different market potential value. A potential market can provide valuable information for a good forecast. From the managements’ perspective, proper planning and development is done to maintain the places based on the forecast. Grey Bass diffusion model, a popular model in handling forecast of a new product with limited data, is expected to forecast two ecotourism resorts, Tanah Aina Fahad and Tanah Aina Farrah Soraya using different market potential value. Yearly data from 2014 until 2018 from both tourism products are collected. The values of potential markets are calculated from the percentage number of visitors to Raub district since the new tourism products are located in Raub, Pahang. This study indicates that different market potential give significant impact on the accurate forecast. The closer the value of potential market calculated from percentage to the actual value, the higher the accuracy of the forecast.